Kepastian Hukum Peralihan Hak Atas Tanah Sengketa (Studi Kasus SHM/1045 Lontar) - Alviano Boyko Wijaya (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This paper discusses the issue concerning of legal certainty over the transfer of disputed land rights in relation to the principle of good faith. The research usud is doctrinal legal research. The results of this study can be concluded that the legal certainty of land rights can be proven by a certificate as strong evidence as stipulated Article 19 Paragraph (2) C UUPA Jo. Article 32 paragraph (2) PP 24/1997. The transfer of land rights carried out by the holder of SHM/1045 Lontar with the recipient of the release of land rights is in accordance with the principle of goof faith as stipulated in article 1338 paragraph (3) Jo. SEMA 4/2016 eventhough the are claims form the other parties, the transfer of land rights is not null and void as stipulated in article 1320 BW Jo. 1337 BW.Key words: Legal Certainty, Transfer of Rights, Land Dispute, SHM/1045 Lontar